2019
DOI: 10.1111/anae.14918
|View full text |Cite
|
Sign up to set email alerts
|

The association of pre‐operative anaemia with survival after orthotopic liver transplantation

Abstract: Summary Anaemia is common in patients with end‐stage liver disease. Pre‐operative anaemia is associated with greater mortality after major surgery. We analysed the association of pre‐operative anaemia (World Health Organization classification) with survival and complications after orthotopic liver transplantation using Cox and logistic regression models. We included patients undergoing their first orthotopic liver transplantation between 2004 and 2016. Out of 599 included patients, 455 (76%) were anaemic befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Although anaemia was not associated with AKI in our study, pre-operative anaemia is an established risk factor for AKI in cardiac patients undergoing coronary bypass surgery [30] (hazard ratio 1.23) as well as after orthoptic liver transplantation (OR 1.72; 95% CI 1.11 -2.67). [31] A large retrospective study in noncardiac surgical patients by Wash et al [32] demonstrated that 29% of patients presented to surgery anaemic. Compared with non-anaemic counterparts, patients with a Hb 10 -12 g/dL had double the odds of postoperative AKI, and those with Hb <8 g/dL had a 3.7-fold risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although anaemia was not associated with AKI in our study, pre-operative anaemia is an established risk factor for AKI in cardiac patients undergoing coronary bypass surgery [30] (hazard ratio 1.23) as well as after orthoptic liver transplantation (OR 1.72; 95% CI 1.11 -2.67). [31] A large retrospective study in noncardiac surgical patients by Wash et al [32] demonstrated that 29% of patients presented to surgery anaemic. Compared with non-anaemic counterparts, patients with a Hb 10 -12 g/dL had double the odds of postoperative AKI, and those with Hb <8 g/dL had a 3.7-fold risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, more transfusion was generally associated with poorer outcome although the authors did not mention a critical threshold in their cohort. 32 Older studies from the 1970s reported a positive immune-modulating effect of transfusions in transplanted patients leading to improved renal graft survival. This effect can still be found on the donor side in modern register studies.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence indicates that preoperative and postoperative anemia is a significant risk factor of post-OLT AKI. 5 Furthermore, intraoperative blood transfusion, especially use of older red blood cells, can significantly increase the risk of post-OLT AKI. 6 Particularly, AKI occurring within 1 week post-OLT was assessed, but the readers were not provided with the occurrence of early postoperative complications.…”
mentioning
confidence: 99%